Influence of pulsed plasma streams processing on wear behavior of steels in different friction conditions - Bandura, A.N.; Bovda, A.M.; Byrka, O.V.; Chebotarev, V.V.; Garkusha, I.E.; Tereshin, V.I.; Tortika, A.S. (Вопросы атомной науки и техники, 2000)
Pulsed plasma streams processing was applied for surface modification of industrial steel samples. Different types of wear tests (pin-on-disk, flat-on-flat, abrasive, cavitation) were carried out for samples irradiated by pulsed nitrogen plasma streams. There was achieved essential decrease of wear and tear of processed surfaces of all kinds of steels including previously thermally quenched ones. Obtained results are of importance for both determination of optimal regimes of plasma streams processing and the most resulting use of pulsed plasma streams for technology purposes, i.e. for identification of wear modes and optimal friction conditions for steels processed by plasma streams.